Multidrug-Resistant Acinetobacter baumannii - Abbo, Aharon (Centers for Disease Control and Prevention, 2005)
To understand the epidemiology of multidrug-resistant (MDR) Acinetobacter baumannii and define individual risk factors for MDR, we used epidemiologic methods, performed organism typing by pulsed-field gel electrophoresis (PFGE), and conducted a matched case-control retrospective study. We investigated 118 patients, on 27 wards, in whom MDR A. baumannii was isolated from clinical cultures. Each case-patient had a control without MDR A. baumannii and was matched for hospital length of stay, ward, and calendar time. The epidemiologic investigation found small clusters of up to 6 patients each with no common identified source. Ten different PFGE clones were found, of which 2 dominated. The PFGE pattern differed within temporospatial clusters, and antimicrobial drug susceptibility patterns varied within and between clones. Multivariate analysis identified the following significant risk factors: male sex, cardiovascular disease, having undergone mechanical ventilation, and having been treated with antimicrobial drugs (particularly metronidazole). Penicillins were protective. The complex epidemiology may explain why the emergence of MDR A. baumannii is difficult to control.